Impact of COVID-19 on increasing female genital mutilation (FGM) in Africa: A study of Tanzania and Nigeria - Emmanuel Michael Massay; Emy Susanti; Sutinah Sutinah (Masyarakat, Kebudayaan dan Politik, 2022)
Women’s sexual and reproductive health and rights (SRHR) have been undermined from time to time due to female genital mutilation (FGM). Women and girls experiencing FGM in many developing countries, including Tanzania and Nigeria. The aim of this study is to investigate the problems that occurred during the COVID-19 pandemic, which contributed to the high rates of FGM in Tanzania and Nigeria. This study uses a qualitative method to see the prevalence of FGM in both countries which has increased since the COVID-19 pandemic. This study is supported by the Patriarchal theory of Sylvia Walby, which explains why men try to oppress and control women as figures who dominate society. The study results show that both Nigeria and Tanzania have seen an increase in FGM amid COVID-19, with school closures placing teenage girls at the highest risk of FGM. The study concludes that the government, private institutions, and other development stakeholders should work together to find solutions to assist communities and families in ending FGM. If these efforts are implemented, then the 2030 sustainable development agenda can become a reality in ending FGM in Nigeria and Tanzania.